Invasive Methicillin-Resistant Staphylococcus aureus USA500 Strains from the U.S. Emerging Infections Program Constitute Three Geographically Distinct Lineages - M. B. Frisch (American Society for Microbiology, 2018)
ABSTRACT USA500 isolates are clonal complex 8 (CC8) Staphylococcus aureus strains closely related to the prominent community- and hospital-associated USA300 group. Despite being relatively understudied, USA500 strains cause a significant burden of disease and are the third most common methicillin-resistant S. aureus (MRSA) strains identified in the U.S. Emerging Infections Program (EIP) invasive S. aureus surveillance. To better understand the genetic relationships of the strains, we sequenced the genomes of 539 USA500 MRSA isolates from sterile site infections collected through the EIP between 2005 and 2013 in the United States. USA500 isolates fell into three major clades principally separated by their distribution across different U.S. regions. Clade C1 strains, found principally in the Northeast, were associated with multiple IS256 insertion elements in their genomes and higher levels of antibiotic resistance. C2 was associated with Southern states, and E1 was associated with Western states. C1 and C2 strains all shared a frameshift in the gene encoding AdsA surface-attached surface protein. We propose that the term “USA500” should be used for CC8 strains sharing a recent common ancestor with the C1, C2, and E1 strains but not in the USA300 group. IMPORTANCE In this work, we have removed some of the confusion surrounding the use of the name “USA500,” placed USA500 strains in the context of the CC8 group, and developed a strategy for assignment to subclades based on genome sequence. Our new phylogeny of USA300/USA500 will be a reference point for understanding the genetic adaptations that have allowed multiple highly virulent clonal strains to emerge from within CC8 over the past 50 years.